IMPROVING THE METHODOLOGY OF TEACHING ENGLISH USING ELEMENTS OF DISTANCE LEARNING - Qodirqulova Munisa, (TADQIQOTLAR, 2026)
This  article  is  dedicated  to  enhancing  the  methodology  of  teaching  English through the integration of distance learning elements. It explores the application of distance learning technologies in the teaching process, the development of students' independent working skills, and the creation of an interactive learning environment. The article discusses the advantages of distance learning, the integration of modern platforms into the educational process, and offers recommendations for educators. The ultimate goal is to make the process of learning English more effective by improving teaching methodologies.